GAMBARAN KEHAMILAN REMAJA DITINJAU DARI UMUR, PENYEBAB KEHAMILAN DAN KONTAK PERTAMA DENGAN TENAGA KESEHATAN DI WILAYAH KERJA PUSKESMAS SIKUMANA KOTA KUPANG - Ummu Zakiah; Hironima Niyati Fitri (STIKes CHMK, 2020)
Teenage pregnancy is a pregnancy that occurs in women aged 14-20 years in both married and unmarried women. Teenage pregnancy is a health problem that is always increasing throughout the world, including in Indonesia. The survey results of the Indonesian Family Planning Association (PKBI) in 2006-2008 showed that 29.5 - 31.3% in NTT had had premarital sex. From the survey results it was also found 39 per 100,000 NTT teenagers gave birth at the age of 15-19 years. In 2017 a total of 548 incidents of teenage pregnant women in the city of Kupang and a total of 90 (6.6%) incidents of teenage pregnancy were found in adolescent girls in the Sikumana area of ​​Kupang City. This study aims to determine the description of adolescent pregnancy in terms of age, cause of pregnancy and first contact with health workers in the area of ​​Sikumana Health Center, Kupang City. The number of samples in this study were 138 young women who experienced teenage pregnancies in January 2018 s. d July 2019. This research is a quantitative study with descriptive methods. The results of the study showed that as many as 121 (87.7%) of young women became pregnant at the end of their teens (16-19 years) with the cause of pregnancy namely free sex (137) (93.3%) and during pregnancy most of the young women those who experienced teenage pregnancy made contact with health workers or performed antenatal care examinations in the second trimester as many as 78 (56.5%). Maternal deaths in pregnant and childbearing women under the age of 20 are 2-5 times higher than in maternal deaths at the age of 20 to 29 years and increase again at the age of 30-35 years. Efforts are needed to promote reproductive health to adolescent girls to avoid pregnancy at adolescence. Keywords: pregnant, teenagers